UV-absorbing mycosporine-like amino acids in the eyes of temperate marine and freshwater fish species - Bonin, Jane; Hammerle, Fabian J.; Ganzera, Markus; Krumme, Uwe; Karsten, Ulf (Frontiers in Marine Science, 2024)
Ultraviolet radiation (UVR) is the photochemically most reactive waveband of incident solar irradiation. Despite high absorption in aquatic environments, UVR causes numerous biochemical, genetic and cytotoxic effects in aquatic organisms. To counteract UVR stress, many of those species are able to synthesize and accumulate or to acquire UV-sunscreen compounds for photoprotection from their diet. The most abundant UV-sunscreens in marine and freshwater organisms are mycosporine-like amino acids (MAAs), which exhibit high molar extinction coefficients in the UVR-range along with a strong photo-and heat-stability.In this study we investigated the qualitative and quantitative MAA distribution patterns in the eyes of 39 fish species, mainly from the temperate northern hemisphere (Baltic Sea, Northern Atlantic) using state-of-the-art analytical methods. The fish eyes of most investigated species (33 taxa) contained MAAs, between one and seven different compounds. The MAAs palythine, asterina-330, palythene and usujirene were present (as previously reported), and 2 three new compounds aplysiapalythine A, porphyra-334 and shinorine identified. Total MAA concentrations covered a wide range from trace amounts to > 4.2 mg g -1 dry weight, thereby providing the first quantitative data on MAAs in fish eyes. The highest MAA contents were measured in Sprattus sprattus, which are comparable to those of intertidal red seaweeds. The trophic transfer of MAAs from primary producers via zooplankton to the fish is discussed together with the localization in the fish eye as well as possible additional functions.